Using the past to understand future property acquisitions: an examination of historic voluntary and mandatory household relocations - Elyse Zavar; Sherri Brokopp Binder; Alex Greer; Amber Breaux (Natural Hazards, 2022)
As climate change continues to exacerbate hazard losses across the USA, many communities are seeking to permanently reduce their hazard exposure by relocating households out of high-risk areas. In the USA, governments have traditionally relocated households using two mechanisms: buyout programs and eminent domain. Although both programs acquire private properties for public ownership and use, buyout programs are defined as voluntary by government entities, whereas eminent domain is compulsory. For decades, Harris County, Texas, has used both voluntary buyouts and eminent domain to relocate households out of flood-prone areas for different uses; buyouts produce open space, whereas eminent domain is used for flood risk reduction projects Although the literature on buyouts continues to grow, especially related to managed retreat, little research considers mandated relocation in response to hazard in the USA despite the increasing potential and calls for mandated relocations due to sea level rise and other climate-induced hazards. To address this gap in the literature, we analyze county records spanning approximately 100 years to examine the geographic patterns related to Harris County’s use of eminent domain and buyouts programs to mitigate flood hazards. Integrating these records into a Geographic Information System, this novel study is the first to compare these two programs and consider the implications for future managed retreat.